Pengembangan Materi Pendidikan Agama Islam Berbasis Nilai-nilai Kerukunan - Siti Khoirun Nisak (STIT Al-Quraniyah Manna, 2021)
The emergence of several conflicts in this country has made some parents anxious about how their child's life will be. Even though children are the nation's next generation. From this, it is necessary to develop Islamic Education material based on the values of harmony. The purpose of applying the values of harmony in the school environment is to create a harmonious atmosphere for teachers and students. So that it can have an effect on a wider environment outside the school that carries the values of harmony. The method used is the literature review from books and research journals. The results of this research, the development of the material carried out: 1. Giving some understanding of the concept, 2. Giving examples of actions or actions that have the value of harmony, 3. Asking students what students think and how students respond to a problem, 4. If the student's answer deviates from the value of harmony, the teacher corrects which one is correct, 5. Inviting students to practice actions that contain the values of harmony Keywords: Islamic Material Development, Islamic Education, Harmony Islamic Education